Genetic models for epithermal gold deposits and applications to exploration - Veselinović, Milica (Rhodes University, Faculty of Science, Department of Geology, 1992)
Epithermal gold deposits are the product of large-scale hydrothermal systems in tectonically active regions. They form at shallow crustal levels where the physico-chemical conditions change abruptly. Two major groups of epithermal gold deposits can be distinguished based on their genetic connection with: A) Copper-molybdenum porphyry systems and B) Geothermal systems related to volcanic centres and calderas. Epithermal gold deposits connected with geothermal systems encompass three major types: adularia-sericite, acid-sulphate and disseminated replacement (the Carlin-type). Their essential ingredients are: high heat source which leads to convection of groundwater in the upper crust; source of hydrothermal fluid, metals and reduced sulphur; and high-permeability structures which allow fluid convection and metal deposition. Mixing of these ingredients leads to the formation of epithermal gold deposits throughout crustal history, without any restriction on age. The ores were deposited from near-neutral (adularia-sericite type and some of the Carlin-type) to acidic (acid-sulphate type and porphyry-related epithermal gold deposits), low-salinity, high C0₂ and high H₂S fluids, which were predominantly meteoritic in origin. The transport capability of deep fluids in epithermal hydrothermal systems may be shown to be dependent largely on their H₂S content and, through a series of fluid mineral equilibria, on temperature and on C0₂ content. The most common mechanisms of ore deposition are boiling (phase separation), mixing of fluids of different temperatures and salinities, reaction between them and wall rocks, dilution and cooling. An understanding of genetic models for epithermal gold deposits provides the basis for the selection of favourable areas for regional to prospect-scale exploration.
Keywords: Gold ores -- Geology; Hydrothermal deposits